1993
DOI: 10.2465/ganko.88.313
|View full text |Cite
|
Sign up to set email alerts
|

K-Ar ages of the Miocene Ryozen basalts from the northern margin of the Abukuma Highland, Japan.

Abstract: K-Ar ages were determined for Miocene Ryozen basalts from east of Fukushima City. Northeast Japan. The Ryozen basalts mainly comprise primitive basalt lava flows of the island are tholeiite series with subordinate amounts of pyroclastic flows. Ten basalt specimens gave almost identical K-Ar ages of 12.4-16.0 Ma, corresponding to Middle Miocene age. If we combine the data of previous studies with the present ones, we can conclude that the Ryozen district have two periods of activities in Miocene. A weak andesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The age of Takadate samples in this study is 12.2–14.7 Ma, corresponding to the more recent phase. Two eruption phases have been also reported for Ryozen at 21.3–22.1 Ma and 12.4–16.0 Ma [ Tsunakawa et al , 1983; Ohki et al , 1993a]. Among the samples from Ryozen, RZ‐4 shows a younger age than the others.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The age of Takadate samples in this study is 12.2–14.7 Ma, corresponding to the more recent phase. Two eruption phases have been also reported for Ryozen at 21.3–22.1 Ma and 12.4–16.0 Ma [ Tsunakawa et al , 1983; Ohki et al , 1993a]. Among the samples from Ryozen, RZ‐4 shows a younger age than the others.…”
Section: Resultsmentioning
confidence: 96%
“…Previous K‐Ar age data dated magmatic activity at Choshi at 21 Ma [ Seno et al , 1986], the Tomari volcanism at 14 Ma [ Watanabe et al , 1993] and the Mitaki volcanism at 8 Ma [ Uto et al , 1989]. The binary volcanic activities have been identified for Ryozen formations (22 and 15 Ma [ Tsunakawa et al , 1983; Ohki et al , 1993a]) and the Takadate formations (22 and 15 Ma [ Uto et al , 1989]). We chose the samples from the Iwate Volcano as a representative reference of the Quaternary NE Japan arc (Figure 1).…”
Section: Geological Background and Samplesmentioning
confidence: 99%
“…These volcanic rocks can be classified mostly to the island arc tholeiite series and calc-alkaline series, however, from their mineralogy and major and trace element chemistry, they can be partially classified to the alkaline series. Ohki et al 1993). This evidence suggests that the Ryozen sequence has two different groups of ages of -22Ma and 13-16Ma.…”
Section: Volcanism Of Oligocene To Recent Agementioning
confidence: 85%
“…However recent K-Ar age determinations for the Miocene volcanic rocks showed that they were formed by a nearly simultaneous volcanism of Volcanic fronts in the Northeast lapan arc 89 Middle Miocene age (13-16Ma) (Shuto et al 1992a;Ohki et al 1993;Watanabe et al 1993). These rocks were composed mainly of andesites with subordinate amounts of basalts and dacites and occurred in the trench side of the NE Japan arc.…”
Section: Volcanism Of Oligocene To Recent Agementioning
confidence: 99%
See 1 more Smart Citation